2018
DOI: 10.3102/0002831218758668
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Equity-Oriented STEM-Rich Making Among Youth From Historically Marginalized Communities

Abstract: The maker movement has evoked interest for its role in breaking down barriers to STEM learning. However, few empirical studies document how youth are supported over time in STEM-rich making projects or their outcomes. This longitudinal critical ethnographic study traces the development of 41 youth maker projects in two community-centered making programs. Building a conceptual argument for an equity-oriented culture of making, the authors discuss the ways in which making with and in community opened opportuniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(80 citation statements)
references
References 32 publications
1
76
1
2
Order By: Relevance
“…Together, our study, along with those studies in VR more broadly, encourages researchers and teachers to explore the dynamic potential of VR 360 to impact diverse students' learning and sense of connection to the discipline as a function of leveraging these students' local contexts as sites where science can be learned, an affordance emphasized by equity‐focused K‐16 STEM education research more broadly (Calabrese Barton & Tan, ; Garibay, ; Kayumova, McGuire, & Cardello, ; Vakil, ; Vossoughi, Hooper, & Escudé, ). Thus, while aligning curriculum to pursue relevant ways of teaching and learning science continues to be a struggle for science teachers (Braaten & Sheth, ; Mensah et al, ; Rodriguez, ), this struggle, specifically in elementary science, has been shown to be ameliorated by research–practice partnerships where design elements that contextualize science content in students' local contexts and leverage students' identities afford students the chance to embrace a nuanced type of learning, as well as the capacity to apply what they have learned (Buxton, ; Djonko‐Moore, Leonard, Holifield, Bailey, & Almughyirah, ; Upadhyay, Maruyama, & Albrecht, ).…”
Section: Implications and Principal Contribution To The Fieldmentioning
confidence: 88%
See 1 more Smart Citation
“…Together, our study, along with those studies in VR more broadly, encourages researchers and teachers to explore the dynamic potential of VR 360 to impact diverse students' learning and sense of connection to the discipline as a function of leveraging these students' local contexts as sites where science can be learned, an affordance emphasized by equity‐focused K‐16 STEM education research more broadly (Calabrese Barton & Tan, ; Garibay, ; Kayumova, McGuire, & Cardello, ; Vakil, ; Vossoughi, Hooper, & Escudé, ). Thus, while aligning curriculum to pursue relevant ways of teaching and learning science continues to be a struggle for science teachers (Braaten & Sheth, ; Mensah et al, ; Rodriguez, ), this struggle, specifically in elementary science, has been shown to be ameliorated by research–practice partnerships where design elements that contextualize science content in students' local contexts and leverage students' identities afford students the chance to embrace a nuanced type of learning, as well as the capacity to apply what they have learned (Buxton, ; Djonko‐Moore, Leonard, Holifield, Bailey, & Almughyirah, ; Upadhyay, Maruyama, & Albrecht, ).…”
Section: Implications and Principal Contribution To The Fieldmentioning
confidence: 88%
“…As we report here, science education research and practice can embrace a context‐specific relationality —a “cultural view foreground[ing] how learning is a relational activity in terms of time (past, present, future), [and] place (previous and current home)” (Calabrese Barton & Tan, , p. 766)—such that the development of three‐dimensional learning experiences for youth does not seem arduous and impractical in the face of the multiple obligations elementary teachers face. This is of particular importance for urban elementary science teachers who struggle to design and embrace responsive pedagogies that both leverage this reform‐minded agenda and adopt a relevant science content application (cf.…”
Section: Background Literaturementioning
confidence: 99%
“…We take a critical justice stance toward defining equity. In taking this stance, we consider the importance of (a) access to resources and opportunities (b) that recognize, respect, and value differences among people and contexts (c) while also disrupting, rather than reproducing, injustice and promoting justice-oriented futures (Calabrese Barton & Tan, 2018).…”
Section: Consequential Learning and Rightful Presencementioning
confidence: 99%
“…To address concerns about future generations of scientists being ignorant of how cultures impacts science, The Framework (National Research Council, ) argues that students should see that their lived experiences, science identities, and cultural and linguistic resources help advance science learning (e.g., Brickhouse, Lowery, & Schultz, ; Calabrese Barton, & Tan, ; Pugh, McGinty & Bang, ). Science taught in this way empowers learners as active architects of their own meaning.…”
Section: Theme 2: Science Practice and Powermentioning
confidence: 99%
“…A broader and more inclusive science education will build an expansive and shared epistemology—one that is not silencing but empowers youth to draw on their local knowledge as foundationally important to science work (Calabrese Barton & Tan, ; Harding, ). Such an expansive view of science allows us to recognize the benefits that Western science has contributed to our world, as well as the ways that Western culture and values have influenced the ways we think about science knowledge (Mahony & Hulme, ).…”
Section: Implications For Science Educationmentioning
confidence: 99%